FI’IL MAZID DALAM AL-QUR’AN JUZ 1 (TINJAUAN MORFOSEMANTIS) - Hidayah, Nur; Busri, Hasan; Kuswardono, Singgih (Lisanul Arab: Journal of Arabic Learning and Teaching, 2018)
Fi'il mazid are verbs that have affixation or fi'il which gain the addition of ziyadah charity. Ziyadah is one of the most commonly occurring morphological processes in every word or kalimah in Arabic and involves some elements in the process, namely the basic form, affix, and grammatical meanings produced. Sometimes this process make difficulity for Arabic learners to understand Arabic word. Therefore, an analysis of augmentative verb is required. The purpose of this research is to know all kinds of things about augmentative verbs with the pattern/wazan, affixation type, verb type, and the semantic meaning contained in first section of Koran. This research is a qualitative research with library research design. The data in this research are augmentative verbs or fi'il mazid sourced from the first section of Koran. Technique of collecting data uses documentation technique and technique of sampling uses purposive sampling. And the method of data analysis uses distributional technique for the direct element. The results of this research show that in first section of Koran there are 179 fi’il mazid. But the researchers took and analyzed 75 data samples with purposive sampling technique. Abstrak ___________________________________________________________________ Fi’il mazid merupakan fi’il yang mengalami ziyadah atau fi’il yang mendapatkan penambahan charf ziyadah. Ziyadah merupakan salah satu proses morfologis yang paling sering terjadi dalam setiap kalimah/kata dalam bahasa Arab dan melibatkan beberapa unsur dalam prosesnya, yaitu berupa bentuk dasar, afiks/charf ziyadah, dan makna gramatikal yang dihasilkan. Terkadang hal inilah yang menyulitkan para pembelajar bahasa Arab dalam memahami kalimah Arab. Oleh sebab itu, diperlukan suatu analisis tentang fi’il mazid. Tujuan dari penelitian ini yaitu untuk mengetahui bentuk fi’il mazid dalam Al-Qur’an juz 1 beserta wazan, jenis ziyadah, afiks/charf ziyadah, jenis fi’il, dan peran semantisnya. Penelitian ini merupakan penelitian kualitatif dengan desain studi pustaka (library research). Data dalam penelitian ini yaitu berupa fi’il mazid/ fi’il mazid yang bersumber dari Al-Qur’an juz 1 dengan teknik pengumpulan data berupa dokumentasi serta instrumen penelitian berupa kartu data dan lembar rekapitulasi. Hasil penelitian menunjukkan bahwa pada Al-Qur’an juz 1 terdapat 179 fi’il mazid. Namun peneliti mengambil dan menganalisis 75 sampel data dengan teknik purposive sampling.